Pengaruh Proses Tempa Dingin Terhadap Sifat Mekanik Dan Struktur Mikro Baja Karbon Tinggi Dengan Paduan Rendah 1.92%C-0.73%Cr-2%Ni Berbasis Laterit Untuk Aplikasi Grinding Ball - rewata, bill (JURNAL POWERPLANT, 2020)
The development of Indonesia’s steel industry is still constrained by the limitations of raw materials and energy. In terms of raw materials, Indonesia does not have high levels of iron ore in sufficient quantities. The limitation of iron ore will be overcome by the use of laterite iron (nickel) ore. When melted into steel, this type of ore will produce steel with a nickel content between 2-3%. A number promises the emergence of superior traits, especially for producing high strength steel which is very much needed in the construction of infrastructure in Indonesia. The addition of chromium to laterite steel aims to increase strength, hardness, suppleness, wear resistance to rust and acid. Going through the forging process can also cause grain distortion and increase strength and hardness, improve ability. The availability of natural resources makes laterite ore a potential as a basis for independence to meet national steel needs. By carrying out hard tests, wear resistance tests, micro tests can be known the mechanical properties of Cr-Ni laterite steel.